Introduction to special focus issue: teaching artists and arts education policy. Issue 2 (3rd April 2023) - Conway, Colleen; Inendino, Sarah; Vecchio, Mike
Abstract: This Special Focus issue of Arts Education Policy Review highlights the work of diverse scholars who consider policies at the local and organizational levels that impact the preparation and work of dance, music, and theater teaching artists in P-12 school and community youth development settings. Doug Risner and I (Colleen) were Guest Editors for this issue and are excited to bring this scholarship forth. We (Colleen, Sarah, Mike) begin this introduction discussing the emergence of the term teaching artist. The middle section addresses the preparation and professional development of teaching artists as well as the varied types of programs employing teaching artists. The introduction ends by situating the six articles in this Special Focus issue within arts education policy and the concepts discussed.